Virtual reality on vision improvement - Yu, Haitao (2017)
VR has become a hot word in recent years, it can be implemented in many different areas to help people to fasten their work flow and improve their productivity. In this paper, we make use of VR Technologies on nearsightedness treatment to help doctors to better treat their patients. For better understanding of the concept of curing shortsightedness. Many paper and websites have been studied. Founded that although eye exercise may not cure nearsightedness totally, it is a good way to train you eye by increasing eye function to focus better and reducing eye stress. Later in this paper, there will be introduction about software and hardware we used in this project. We will also discuss the project detail of implementing eye exercise in the VR Technology and the advantage of using this high-end technology. Thus, a study of a combination of new technology and old exercise methods come out and hope to provide useful function in prevention and treatment in eye disease.